PENGARUH PENDEKATAN SETS BERBASIS KEARIFAN LOKAL TERHADAP MINAT BERWIRAUSAHA DALAM MATERI KOLOID PADA SISWA - Asnawati, Asnawati; Hairida, Hairida; Melati, Husna Amalia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrakThis research aimed to determine the difference in interest in entrepreneurship and the magnitude of the influence of the local wisdom-based SETS approach on students' interest in entrepreneurship in colloidal material. The population of this research was class IX the students of Pontianak 9 High School in the academic year 2017/2018. The sampling technique used was purposive sampling . The design used in this study was nonequivalent control group design, obtained class IX IPA 2 as the experimental class using the SETS approach based on local wisdom and class IX IPA 3 as the control class using a conventional approach. The results of this research showed that there was a difference between the interest in the experimental class entrepreneurship and the control class and there also significant influence of the local wisdom-based SETS approach on students' interest in entrepreneurship. The magnitude of the influence of the SETS approach is based on local wisdom towards the interest in entrepreneurship in colloidal material is 44.84%. The SETS approach to colloidal material gives a difference in interest in entrepreneurship between the experimental class and the control class and the influence on the interest in entrepreneurship at the Pontianak High School 9.Keyword: SETS Approach, Local Wisdom, interest in entrepreneurs